Mitsui model with diagonal strains: A unified description of external pressure effect and thermal expansion of Rochelle salt NaKC₄H₄O₆·4H₂O - Moina, A.P.; Levitskii, R.R.; Zachek, I.R. (Condensed Matter Physics, 2011)
We elaborate a modification of the deformable two-sublattice Mitsui model of [Levitskii R.R. et al., Phys. Rev. B. 2003, 67, 174112] and [Levitskii R.R. et al., Condens. Matter Phys., 2005, 8, 881] that consistently takes into account diagonal components of the strain tensor, arising either due to external pressures or due to thermal expansion. We calculate the related to those strains thermal, piezoelectric, and elastic characteristics of the system. Using the developed fitting procedure, a set of the model parameters is found for the case of Rochelle salt crystals, providing a satisfactory agreement with the available experimental data for the hydrostatic and uniaxial pressure dependences of the Curie temperatures, temperature dependences of spontaneous diagonal strains, linear thermal expansion coefficients, elastic constants cijE and ci₄E, piezoelectric coefficients d₁i and g₁i (i=1,2,3). The hydrostatic pressure variation of dielectric permittivity is described using a derived expression for the permittivity of a partially clamped crystal. The dipole moments and the asymmetry parameter of Rochelle salt are found to increase with hydrostatic pressure.